Constitutive models characterisation for XC48 steel in compression by a parametric identification technique. (4th August 2014) - Langrand, B.; Markiewicz, E.; Drazetic, P.; Geoffroy, P.; Petitniot, J.L.; Fabis, J.
This paper deals with a parametric identification technique, based on conjugate gradient methods. As part of this research, compression tests are performed on a XC48 steel (AFNOR norm 1048AISI), which is strain rate sensitive. Two kinds of specimen, tubular and cylindrical 'dumbbells', are tested at different strain rates, from to 10 −3 to 130s −1, and for impact velocities ranging from 5 mm/mn to 6 m/s. The parameters of the Johnson–Cook constitutive model are evaluated directly from the XC48 steel compression stress–strain diagrams expressed in terms of true stress and strain measurements. These parameters are next used as input data for a FE crash simulation of the tubular specimen. Comparison with experimental results prove the validity of the identified parameters.